2019
DOI: 10.1021/acs.est.8b06965
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Superemitter Natural Gas Well Pads in the Marcellus Shale

Abstract: A large-scale study of methane emissions from well pads was conducted in the Marcellus shale (Pennsylvania), the largest producing natural gas shale play in the United States, to better identify the prevalence and characteristics of superemitters. Roughly 2100 measurements were taken from 673 unique unconventional well pads corresponding to ∼18% of the total population of active sites and ∼32% of the total statewide unconventional natural gas production. A log-normal distribution with a geometric mean of 2.0 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
66
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(77 citation statements)
references
References 30 publications
8
66
3
Order By: Relevance
“…For example, BHGE performed well in the class of leaks >8 scfh and could be re-tested with more samples in that regime. This is especially important considering that a recent study of emissions in the Marcellus shale found that the average emission rate at the pad-level was 5.5 kg/h, corresponding to ~3 50 scfh (Caulton, et al, 2019). However, these are pad-level estimates, and component-level emissions can be significantly smaller -testing at the METEC facility between 0-15 scfh therefore provides a reasonable test of performance for technologies that detect emissions component-level detection.…”
Section: Discussionmentioning
confidence: 99%
“…For example, BHGE performed well in the class of leaks >8 scfh and could be re-tested with more samples in that regime. This is especially important considering that a recent study of emissions in the Marcellus shale found that the average emission rate at the pad-level was 5.5 kg/h, corresponding to ~3 50 scfh (Caulton, et al, 2019). However, these are pad-level estimates, and component-level emissions can be significantly smaller -testing at the METEC facility between 0-15 scfh therefore provides a reasonable test of performance for technologies that detect emissions component-level detection.…”
Section: Discussionmentioning
confidence: 99%
“…This decrease is driven primarily by projected decreases in emissions from the energy sector, despite a 50% increase in gas production and a greater than 200% increase in oil production during the 10 year period (US Energy Information Administration, 2020b). Over the last several years, various atmospheric studies monitoring emissions from O&G from individual wellpads (Caulton et al, 2019;Rella et al, 2015;Robertson et al, 2017), basins (Barkley et al, 2017;Karion et al, 2013Karion et al, , 2015Peischl et al, 2015Peischl et al, , 2016Peischl et al, , 2018Pétron et al, 2012Pétron et al, , 2014, and entire regions have consistently found emission rates larger than the EPA inventory, raising concerns of a broad underestimation of leaks from the O&G sector (Alvarez et al, 2018). However, large-scale CH 4 inversion studies involving the US have not been as conclusive, with differing findings as to the accuracy of inventory emissions from O&G, animal agriculture, and wetlands (Maasakkers et al, 2019;Miller et al, 2013;Sheng et al, 2018;Yu et al, 2020).…”
mentioning
confidence: 99%
“…EPA inventory estimates (Barkley, Lauvaux et al, 2019;Caulton et al, 2019 Alvarez et al (2018). However, in all of these comparisons, we note that the year each study took place varies, such that differences in the solution may include changes due to temporal variability in the O&G activity of a basin.…”
Section: 1029/2020jd034194mentioning
confidence: 99%